Energy efficient WSN Protocols: A Survey - Barman, Utpal; Mundra, Amit; Talukdar, Kunal Gunjan; Goswami, Mrinal; Bhowmick, Pranoy (International Journal of Computer Sciences and Engineering, 2025)
The wireless sensor networking mainly suffers from the fact that the nodes have low energy backup. Some issues in WSNs are that sensor nodes have constrained in terms of processing power, communication bandwidth, and storage space. Due to low energy backup several nodes may die out soon and there may be loss of data. Various routing algorithm have been developed to increase the lifetime of the network. Some of the types of routing protocol are cluster based routing protocol, chain based routing protocol, hierarchical routing protocol and hybrid routing protocol .In this paper we discuss the various protocols such as LEACH, PEGASIS, IEEPB, PDCH, TEEN, APTEEN, CCM, CCBRP, TSCP and see how they are simulated.